Caspase-9: A Multimodal Therapeutic Target With Diverse Cellular Expression in Human Disease - Avrutsky, Maria I.; Troy, Carol M. (Frontiers in Pharmacology, 2021)
Caspase-9, a cysteine-aspartic protease known for its role as an initiator of intrinsic apoptosis, regulates physiological cell death and pathological tissue degeneration. Its nonapoptotic functions, including regulation of cellular differentiation/ maturation, mitochondrial homeostasis, and autophagy, reveal a multimodal landscape of caspase-9 activity in health and disease. Recent work has demonstrated that caspase-9 can drive neurovascular injury through nonapoptotic endothelial cell dysfunction. Healthy tissues maintain low basal levels of caspase-9 activity, rendering pathologic caspase-9 activation a tractable target for therapeutic interventions. Several strategies enable selective inhibition of caspase-9 in animal disease models, such as overexpression of dominant negative caspase-9 mutants and pharmacological inhibition using the Bir3 domain of XIAP, an endogenous selective inhibitor of caspase-9. CASP9 polymorphisms have been linked with various cancers, neurological disorders, autoimmune pathologies and lumbar disc disease. However, the mechanistic implications of caspase-9 expression and activation remain indeterminate in many cell types and conditions. This review examines clinical evidence of caspase-9 signaling pathways and cellular localization in human disease, including acute and chronic neurodegeneration, retinal neuropathy, slow-channel myasthenic syndrome, lumbar disc disease, cardiomyopathies, atherosclerosis and autoimmune disease.